THE EFFECTIVENESS OF BRAND SUBSTANTIVE CHECKS ESSENTIAL STANDARDS IN ONLINE REGISTRATION - Alifkha Herlyanda Putra putra; Indah Sri Utari Utari (Law Research Review Quarterly, 2026)
This study examines the effectiveness of the essential standards of brand substantive examination in the online registration system in Indonesia. A sociological juridical approach is used to analyze the gap between legal norms and implementation practices. Hans Kelsen's theory of validity and Lawrence Friedman's theory of legal effectiveness became the main framework of analysis. The findings of the study show that Article 20 and Article 21 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications have formulated adequate parameters regarding discriminating power, similarity in essence, and bad faith. However, the effectiveness of its implementation is constrained by three fundamental problems. First, the abstract character of the norm of equations basically opens up a wide space for interpretation and creates inuniformity of judgment. Second, the capacity of human resources for inspectors has not been optimal, characterized by weak compliance with registration guidelines and the lack of quality assurance mechanisms. Third, the technical limitations of digital systems in detecting non-textual similarities such as phonetic and conceptual aspects. The accumulation of these obstacles has implications for the inconsistency of examination results, the high rejection rate with a ratio of one to four, and an increase in appeals. This study recommends the simultaneous strengthening of the three Friedman elements through the improvement of interpretation guidelines, systematic enhancement of the capacity of examiners, and the development of a system algorithm capable of detecting non-textual similarities in order to realize a trademark registration system that is not only procedurally efficient, but also able to ensure legal certainty and fair protection of trademark rights.